2009
DOI: 10.1002/ajpa.21104
|View full text |Cite
|
Sign up to set email alerts
|

Migration and diversity in Roman Britain: A multidisciplinary approach to the identification of immigrants in Roman York, England

Abstract: Previous anthropological investigations at Trentholme Drive, in Roman York identified an unusual amount of cranial variation amongst the inhabitants, with some individuals suggested as having originated from the Middle East or North Africa. The current study investigates the validity of this assessment using modern anthropological methods to assess cranial variation in two groups: The Railway and Trentholme Drive. Strontium and oxygen isotope evidence derived from the dentition of 43 of these individuals was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 65 publications
4
80
0
1
Order By: Relevance
“…The presence of individuals with African ancestry is not unexpected, as studies from other urban centres in Roman Britain have found people with this ancestry and/or mobility isotope result (Leach, et al, 2010a(Leach, et al, , 2009a and our results combined with the funerary evidence (Ridgeway, et al, 2014) for these individuals, supports the findings of Eckardt and colleagues who (2014) show that childhood origin and ancestry are not always reflected in a person's burial identity. The people with Asian ancestry are the first to be reported from Roman Britain however, this is cautiously asserted because the method we applied is based on more recent populations, and we recognise that morphology is subject to temporal and spatial variation.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The presence of individuals with African ancestry is not unexpected, as studies from other urban centres in Roman Britain have found people with this ancestry and/or mobility isotope result (Leach, et al, 2010a(Leach, et al, , 2009a and our results combined with the funerary evidence (Ridgeway, et al, 2014) for these individuals, supports the findings of Eckardt and colleagues who (2014) show that childhood origin and ancestry are not always reflected in a person's burial identity. The people with Asian ancestry are the first to be reported from Roman Britain however, this is cautiously asserted because the method we applied is based on more recent populations, and we recognise that morphology is subject to temporal and spatial variation.…”
Section: Discussionsupporting
confidence: 90%
“…The diversity of population and high proportion of migrants in this relatively small sample has identified individuals from the southern reaches of the Mediterranean, a new result for Londinium and provides further evidence for the presence of child-migrants in the settlement (Shaw, et al, 2016 Millard, 2015), throughout the Roman period (Montgomery, et al, 2010, Leach, et al, 2009b, Leach, et al, 2010b and into the Anglo-Saxon period (Groves, et al, 2013).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…By combining this fact with observations confirming a link between the isotopic composition of the oxygen in meteoric water with geographical and climatic conditions occurring in the area in question, it is possible to reconstruct the living area (or habitat) of both individuals and whole human groups (Dupras and Schwarcz, 2001;Hoogewerff et al, 2001;Kendall et al, 2013;Oelze et al, 2012;Szostek 2009;White et al, 2004aWhite et al, , 2004bWłodarczak et al, 2011). As a result, research of this type conducted on skeletal material has become extremely useful for tracking the seasonal wanderings of both animals and people (Britton et al, 2009;Henton et al, 2010;Rubenstein and Hobson, 2004;Shaw et al, 2010) and also the migration of individuals between groups and the origin of settlement(s) in diverse areas (Knudson and Price, 2007;Leach et al, 2009;Prowse et al, 2007;Szostek et al, 2013;White et al, 1998).…”
Section: Introductionmentioning
confidence: 99%